MACRO AND MICROELEMENTS IN THE GASTRO-INTESTINAL TRACT OF RESIDENTS OF ASTRAKHAN REGION - I. V. Zaitsev; A. S. Tanasova (Юг России: экология, развитие, 2015)
Aim. During the life, the organism continuously consumes nutrients that build tissue and produce energy. The source of nutrients is proteins, fats, carbohydrates along with minerals. In this context, the aim of this study was to evaluate the levels of certain elements in the tissue of the stomach, small and large intestine of residents of the Astrakhan region. Materials and methods. We have taken fragments of stomach tissue as material for the study (n = 25), small (n = 25), and large (n = 25), the material has been obtained by sectional study from deaths from acci-dents of healthy individuals aged from 40 to 68 years (average age - 54 ± 0.63 years). The study of features of a cumulative distribution of elements (EM) was performed with atomic absorption spectrophotometry using atomic ab-sorption spectrometer MGA-915. The analysis results are given in mg/kg of dry matter, and were subjected to statis tic processing (Student's t-test, using software Statistica (StatSoft, USA). Identified values were considered signifi-cant at p <0.05. Results. The study revealed that with morphologically similar structures of the tissues of the sto-mach, small and large intestines, similar fluctuations of elements’ accumulation were detected. While gastric tissue accumulates elements more intensively than small and large intestine. Study revealed differences in accumulation of elements depending on gender. For men the average concentration of elements in gastrointestinal tissues was slightly higher (1.3 fold) than for women. Conclusions. One possible factor that contributed to the pathology of the gastrointestinal tract is the increase of the accumulation of trace elements in the gastrointestinal system. Above all, this applies to toxic trace elements in increased amounts found in the tissues of the stomach and intestines, such as cobalt, lead and cadmium, which is an indication of significant environmental pollution.